2019
DOI: 10.1111/and.13266
|View full text |Cite
|
Sign up to set email alerts
|

Influence of post‐thawing thermal environment on bovine sperm characteristics and in vitro fertility

Abstract: Our aim was to evaluate the effects of three thermal environments over time on kinetics, functionality and in vitro fertility of cryopreserved bovine spermatozoa. Four ejaculates from five bulls (n = 20) were cryopreserved. After thawing, semen was evaluated (0 hr), incubated for 4 hr in T36.0 (36.0°C), T38.0 (38.0°C) and T39.5 (39.5°C), and analysed every hour (1 hr, 2 hr, 3 hr, 4 hr). In vitro production of embryos was performed at 0 hr and 4 hr. Sperm motility and cell kinetics (Computer‐Assisted Sperm Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In addition, total motility and PMI during the incubation period significantly decreased to similar values as previously reported in Canchim bull within the same incubation time [43]. Intracellular ROS generation associated with sperm capacitation has been pointed to as a major agent…”
Section: Discussionsupporting
confidence: 85%
“…In addition, total motility and PMI during the incubation period significantly decreased to similar values as previously reported in Canchim bull within the same incubation time [43]. Intracellular ROS generation associated with sperm capacitation has been pointed to as a major agent…”
Section: Discussionsupporting
confidence: 85%
“…However, to explain this astonishing result it should be emphasized that compared to sperm cryopreserved without catalase the addition of this antioxidant did not improve DNA integrity before 12 h after thawing of frozen sperm. In vitro oocytes are fertilized by bovine sperm within the first 4 h after thawing [19]. At this time point sperm frozen without and with catalase showed the same percentage of DNA intact sperm in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, exogenous and endogenous forms of insults (eg high temperature) affect mammalian spermatogenesis and ultimately lead to subfertility and even infertility. 105 Offspring from male mice with a heat‐treated scrotum mated with normal female mice, and exhibited lower weight than those from males without heat treatment. 106 Studies have shown that oxidative stress is a leading outcome of heat damage in spermatogenic cells, 1 , 107 while sperms and oocytes are the most sensitive to heat, 108 , 109 , 110 and the somatic supporting cells such as Sertoli cell in the testis are also affected.…”
Section: Stress Granules Involving In Biological Disordersmentioning
confidence: 99%
“…In most mammals, the testicles are located in the scrotum outside the body cavity, where spermatogenesis usually occurs. Therefore, exogenous and endogenous forms of insults (eg high temperature) affect mammalian spermatogenesis and ultimately lead to subfertility and even infertility 105 . Offspring from male mice with a heat‐treated scrotum mated with normal female mice, and exhibited lower weight than those from males without heat treatment 106 .…”
Section: Stress Granules Involving In Biological Disordersmentioning
confidence: 99%